2021
DOI: 10.1007/s11357-021-00444-9
|View full text |Cite
|
Sign up to set email alerts
|

Animal reservoirs of SARS-CoV-2: calculable COVID-19 risk for older adults from animal to human transmission

Abstract: The current COVID-19 pandemic, caused by the highly contagious respiratory pathogen SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), has already claimed close to three million lives. SARS-CoV-2 is a zoonotic disease: it emerged from a bat reservoir and it can infect a number of agricultural and companion animal species. SARS-CoV-2 can cause respiratory and intestinal infections, and potentially systemic multi-organ disease, in both humans and animals. The risk for severe illness and death with COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 116 publications
0
16
0
Order By: Relevance
“…The attenuated ∆3678 viruses may be pivoted for a veterinarian vaccine. SARS-CoV-2 can infect a variety of animal species, among which cats, ferrets, fruit bats, hamsters, minks, raccoon dogs, and white-tailed deers were reported to spread the infection to other animals of the same species 40 – 44 , and potentially spillback to humans. A live-attenuated ∆3678 vaccine may be useful for the prevention and control of SARS-CoV-2 on mink farms 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The attenuated ∆3678 viruses may be pivoted for a veterinarian vaccine. SARS-CoV-2 can infect a variety of animal species, among which cats, ferrets, fruit bats, hamsters, minks, raccoon dogs, and white-tailed deers were reported to spread the infection to other animals of the same species 40 – 44 , and potentially spillback to humans. A live-attenuated ∆3678 vaccine may be useful for the prevention and control of SARS-CoV-2 on mink farms 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low proportion of participants who would get their pets tested for SARS-CoV-2, even if testing was recommended by the AVMA, is potentially worrisome for human and animal health. The transmission of SARS-CoV-2 among pets could have obvious detrimental impacts on the health status of companion animals, but it could also lead to increased cases among humans if pets were to serve as a disease reservoir [ 48 , 49 ]. As described above, data available at the time of data collection indicated that the risk of SARS-CoV-2 transmission among companion animals was exceedingly low [ 44 ] and the AVMA did not recommend routine testing of pets.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of this, the close association between humans and companion animals raised concerns about the potential risks of SARS-CoV-2 transmission from humans to animals (“reverse zoonosis”) and about the possible role infected animals could play in perpetuating the spread of COVID-19 [ 2 , 5 ]. The role of domestic cats ( Felis catus ) has aroused particular interest, because they are one of the most popular companion animals and often establish close and frequent contact with humans [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A novel coronavirus (2019-nCoV) was identified as the causative agent of the disease by Chinese authorities [1], and the disease officially designated as Coronavirus Disease of 2019 (COVID- 19) was classified as pandemic by the World Health Organization (WHO). Afterwards, due to the severe acute respiratory syndrome caused by the new coronavirus, the designation of the virus changed to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) [2].…”
Section: Introductionmentioning
confidence: 99%